Non-indigenous and Invasive Freshwater Species on the Atlantic Islands of the Azores Archipelago - Costa, Ana C.; Balibrea, Ana; Raposeiro, Pedro M.; Santos, Sofia; Souto, Martin; Gonçalves, Vítor (Frontiers in Ecology and Evolution, 2021)
Freshwater systems on remote oceanic islands are particularly vulnerable to biological invasions. The case of freshwater ecosystems in the Azores Archipelago is especially relevant considering the islands’ youth and remoteness, and low natural connectivity. This study presents a review of the introduction and presence of non-indigenous freshwater species in the Azores, retrieved from various historical records, paleoenvironmental reconstructions, published records, and field data from two decades of the Water Framework Directive (WFD) monitoring programs. At least 132 non-indigenous freshwater species have successfully established in the Azores, belonging to several taxonomic groups: cyanobacteria (10), synurophytes (1), desmids (1), diatoms (20), plants (41), invertebrates (45), amphibia (2), and fishes (12). Intentional and accidental introductions have been occurring since the establishment of the first human settlers on the archipelago, impacting freshwater ecosystems. The first reported introductions in the Azores were intentional fish stocking in some lakes. Non-deliberate introductions have recently increased through transport-contaminants (51%) associated with the aquarium trade or agricultural products. In the Azores, the highest number of non-indigenous species occur on the largest and most populated island, São Miguel Island (116), followed by Flores (68). Plants constitute the most representative group of introduced species on all islands, but invertebrates, diatoms, and fishes are also well established on most islands. Among invertebrates, non-indigenous arthropods are the most well-established group on all islands except on the smallest Corvo Island. Many non-indigenous species will likely benefit from climate change and magnified by globalization that increases the probability of the movement of tropical and subtropical species to the Azores. Present trends in international trade, importations, and enhanced connectivity of the archipelago by increasing flights and shipping will probably promote the arrival of new species. Augmented connectivity among islands is likely to improve non-indigenous species dispersal within the archipelago as accidental transportation seems to be an essential pathway for non-indigenous freshwater species already present in the Azores.